A profissionalização na atuação docente da educação infantil - Correia, Lindinalva de Alcântara (2021)
This dissertation is inserted in the discussion of the universe of the teachers’ background and tries to investigate the professionalization in the teaching performance of Early Childhood Education, which has influenced researches and debates in the educational field. This subject appears from the path taken by own professional experiences. The research is based in the phenomenological approach to we understand the teaching perception about the professionalization and its interrelations with the performance. It was precisely for valuing the subject thinking from a unique way in the world experiences that made us to work with a group of eight teachers of Early Childhood Education from the municipality of João Pessoa – PB, trying to analyse the sense that appears from the descriptions of lived experiences by the teachers in the context of the building of the professionalization. This study has as a main purpose to understand the professionalization in the teaching performance in the Early Childhood Education. About the specific purposes, we opted for analysing how happens the professionalization of teachers in the Early Childhood Education; highlight the constuctor elements of the teaching professionalization in the Early Childhood Education; point out to what extent the teachers’ experience is considered by them, constuctor element of the professionalization. We worked with the exploratory qualitative approach, because it allows a better involvement with the object of study. About the empirical research, it was done with five teachers from a CREI and three teachers from a public school from João Pessoa- PB. To acquisition of information we used as research instruments: The observation not participant, the field diary and semistructured interview. About the method of analysis, we opted for the content analysis, as a way of understanding reality, considering, mainly, the social practice of the subjects. Data achieved by these instuments were analyzed and interpreted by categorical analysis, that consists in one of the technics of the analysis of content, and functions by dismemberment of the text into categories aiming to discover what is behind of the words on which you dwell. It was showed that the building of the professionalization in the teaching performance shows challenges, that probably falls upon the absence of important elements for the question of becoming a teacher.